Epidemology Study of Hypertension Based on Risk Factors in Medical Clinic PT. KAI Daop 7 Madiun City Kediri - Hidayat, Poppy; Herminofa, Irsyad; Fadila, Rizki; Rizal, Yusuf; Ahmadi Putri, Nabila Maharani; Janita Putri, Aqmarlia; Rahman, Aulia; Hedo, Dian Jayantari Putri K; Triningsih, Indah; Sasmito, Armando Hadyono Joko; Bekti, Yhen Ari; Aini, Trianike Nor; Ayu E., Mas Roro Dyah; Andayani, Erisa Ariya; Hardiani, Novita; Crystalia; Supangkat, Ismu Dwi; Peristiowati, Yuly (Journal of Global Research in Public Health, 2022)
In Indonesia, the prevalence of hypertension based on Basic Health Research 2018 is 34.1%. Knowing the epidemiological picture of hypertension sufferers at Klinik Mediska PT. KAI Daop 7 Madiun branch of Kediri City in August - October 2020. Data collection techniques with secondary data by total sampling in the form of data on hypertension patients who have been registered in August - October 2020. The number of hypertensive patients in the male gender is 68% and for females is 32%. ages> 65 years 36%, ages 56-65 years 34%, ages 46-55 years 20%, 36-45 years 6%, ages 26-35 years 4%. The remaining 40% of the smoking habit is 60%. had comorbidities 34%. BMI overweight 64%, normal 32%, underweight 4%. The risk factors for hypertension included: male gender, age> 45 years, smoking habits, comorbidities, and high BMI. Promotional and preventive efforts, as well as education, are needed to be related to several risk factors for hypertension to suffer